Extensor Tendon Dislocation at the Metacarpophalangeal Joint of Both Ring Fingers Caused by a Specific Hand Posture in a Shiatsu Therapist - Mariko Kamiya; Gen Sasaki; Kensuke Ikuta; Hideaki Miyamoto; Michio Kimura; Hirotaka Kawano (Case Reports in Orthopedics)
A 43-year-old female shiatsu therapist complained of sudden snapping of the metacarpophalangeal joints (MCPjs) of both ring fingers during a specific hand posture. The extensor tendon of the ring finger was dislocated ulnarly when the MCPj of the ring finger was flexed and deviated ulnarly and the MCPj of the middle finger was extended. Surgical exploration revealed an attenuated radial sagittal band. We plicated the juncturae tendinum of the extensor digitorum communis between the middle and ring fingers and released the ulnar sagittal band partially to centralise the extensor tendon excursion. Twenty-six months postoperatively, the patient regained full active and passive range of motion of all fingers without extensor tendon dislocation or snapping in either hand during work.